Quality Improvement with 5S for School Library - Mondal, Tanmay (Journal of Information and Knowledge, 2020)
Quality improvement is a continuous process. Improvement of overall quality in library services requires systematic guidelines. 5S is an established and easy to implement technique used for the betterment of the workplace environment over a long period of time. The 5S system represents five important concepts for creating, improving and maintaining a well-organized library through a series of activities. Implementation of 5S in school library enhances the overall quality of services and makes the library a learning hub for all stakeholders.